Prognostic significance of miRNA‐1 (miR‐1) expression in patients with chordoma. Issue 5 (5th February 2014) - Duan, Zhenfeng; Shen, Jacson; Yang, Xiaoqian; Yang, Pei; Osaka, Eiji; Choy, Edwin; Cote, Gregory; Harmon, David; Zhang, Yu; Nielsen, G. Petur; Spentzos, Dimitrios; Mankin, Henry; et al.
ABSTRACT Reliable prognostic biomarkers for chordoma have not yet been established. Recent studies revealed that expression of miRNA‐1 (miR‐1) is frequently downregulated in several cancer types including chordoma. The goal of this follow‐up study is to investigate the expression of miR‐1 as a prognostic biomarker and further confirm the functional role of miR‐1 in chordoma cell growth and proliferation. We determined the relative expression levels of miR‐1 and Met in chordoma tissue samples and correlated those to clinical variables. The results showed that miR‐1 was downregulated in 93.7% of chordoma tissues and expression was inversely correlated with Met expression. miR‐1 expression levels also correlated with clinical prognosis. To characterize and confirm the functional role of miR‐1 in the growth and proliferation of chordoma cells, miR‐1 precursors were stably transfected into chordoma cell lines UCH‐1 and CH‐22. Cell Proliferation Assay and MTT were used to evaluate cell growth and proliferation. Restoring expression of miR‐1 precursor decreased cell growth and proliferation in UCH‐1 and CH‐22 cells. These results indicate that suppressed miR‐1 expression in chordoma may in part be a driver for tumor growth, and that miR‐1 has potential to serve as prognostic biomarker and therapeutic target for chordoma patients. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:695–701, 2014.